Practical Approach to International Business Studies in English at Polish Universities - Krystyna Zoladkiewicz; Renata Orlowska (Theory, Methodology, Practice, 2015)
The subject of this paper is the presentation of BA and MA International Business (IB) studies in English as a new practice on the Polish educational market. The main objective of this paper is to examine the IB studies programmes in English at the University of Gdansk - (UG) and to present the practical approach of their functioning combined with some recommendations. The results show that the UG has established competitive and attractive programmes, although at lower cost levels compared to universities in other countries where the IB studies have longer tradition and good reputation. It is considered that IB studies cement the international position of UG. This article presents both quantitative and qualitative data.